Agroindustrial performance of sugarcane (Saccharum spp.) varieties for panela in Barbosa (Colombia). - Barona Rodríguez, Ayda Fernanda; Antolinez Sandoval, Eduar Yovany; López Lopera, Juan Gonzalo; Viveros Valens, Carlos Arturo; Jiménez Vargas, Javier; Ángel Sánchez, Juan Carlos; Ballesteros Araque, Andrea Lizeth; Vargas Orozco, Germán Andrés (Universidad Pedagógica y Tecnológica de Colombia, 2021)
In Colombia, sugarcane production is the second most important line of agricultural production after coffee, 55% of the total cultivated area is dedicated to the production of panela (non-centrifuged sugar - NCS), a task that is carried out in 29 of the 32 departments of the country. Low yields and the loss of genetic quality of the materials currently being cultivated have brought about the need to evaluate new varieties of sugarcane that adapt to different environments and have a high production of panela. Considering the above, between November 2018 and May 2020, by the Colombian Agricultural Research Corporation - Agrosavia, under the agroecological conditions of Barbosa (Santander, Colombia), the agroindustrial behavior of six sugarcane varieties for panela production (CC 11-600, CC 10-450, CC 99-2461, CC 00-3257, CC 91-1606 and CC 00-3771) from the Colombian sugarcane research center - Cenicaña were evaluated; A randomized complete block design was established with four repetitions for agronomic performance and three replicates for industrial evaluation. Agronomically, the genetic materials presented averages of 2.81 m to plant height, 2.8 cm stem diameter, percentage of Diatraea infestation intensity of 10.66% and 118.92 tons of cane per hectare; for the industrial variables, average values of 21.06 °Brix in juice and 12.78 tons of panela per hectare were found; the evaluated variables referring to panela quality were adjusted to those required in the NTC 1311: 2009 and Resolution 000779 of 2006 of the Ministry of Social Protection. Varieties CC 11-600 and CC 00-3267 showed the best agroindustrial performance in the first production cycle.